Efficient, high peak power Tm:YLF laser - Gorajek, Łukasz (Photonics Letters of Poland, 2013)
We demonstrate efficient generation of diode pumped, passively cooled Tm:YLF laser end-pumped by 25-W fiber coupled laser diode. Over 5 W of output power was achieved for 25-W pumping laser and for elongated 120-mm cavity. For the free-running and Q-switching regimes the output spectrum was centered at 1908-nm with linewidth less than 7 nm. In the experiments on active Q-switching up to 5.5 mJ of output energy was demonstrated with pulse duration of 11 ns, corresponding to 0.5 MW of peak power. Full Text: PDF References Jabczynski, J.K., Gorajek, L., "High repetition rate, high peak power, diode pumped Tm:YLF laser," Laser Phys. Lett. 6 (2), 109-112 (2009) CrossRef Sha, J.J., Shen, D.Y., Zhao, T., Yan, X.F., "High power and highly efficient operation of a Tm:YAG laser in-band pumped at 1617 nm", Laser Phys. Lett. 10, 075801 (2013) CrossRef Guillemet, S., "High pulse energy sub-nanosecond Tm-doped fiber laser". Proc. SPIE 8237, Fiber Lasers IX: Technology, Systems, and Applications, 82373V (2012) CrossRef Swiderski, J., Maciejewska, M., Kwiatkowski, J. and Mamajek, M., "An all-fiber, resonantly pumped, gain-switched, 2 ?m Tm-doped silica fiber laser", Laser Phys. Lett. 10, 015107 (2013). CrossRef Swiderski, J. and Michalska, M., "Generation of self-mode-locked resembling pulses in a fast gain-switched thulium-doped fiber laser," Opt. Lett. 38, 1624-1626 (2013) CrossRef Kwiatkowski, J., Jabczynski, J. K., Gorajek, L., Zendzian, W., Jelinkowa, H., Sulc, J., Nemec, M., Koranda, P., "Resonantly pumped tunable Ho:YAG laser", Laser Phys. Lett. 6 (7), 531-534 (2009) CrossRef Kwiatkowski, J., Jabczynski, J.K., Zendzian, W., Swiderski J., Gorajek, L. and Galecki, L., "Resonantly pumped acousto-optically Q-switched hybrid Ho:YAG laser", Laser Phys. Lett. 8 (4), 281-285 (2011) CrossRef Gallian, A., Fedorov, V. V., "Hotpressed ceramic Cr2+:ZnSe gain-switched laser", Opt. Express 14, 11694?11701 (2006) CrossRef Creeden, D., Ketteridge, P., "Mid-infrared ZnGeP2 parametric oscillator directly pumped by a pulsed 2 ?m Tm-doped fiber laser," Opt. Lett. 33, 315-317 (2008) CrossRef Swiderski, J. and Maciejewska, M., "Watt-level, all-fiber supercontinuum source based on telecom-grade fiber components", Appl. Phys. B 109, 177-181 (2012) CrossRef Swiderski, J. and Michalska, M., "Mid-infrared supercontinuum generation in a single-mode thulium-doped fiber amplifier", Laser Phys. Lett. 10, 035105 (2013) CrossRef Swiderski, J., Michalska, M. and Maze, G., "Mid-IR supercontinuum generation in a ZBLAN fiber pumped by a gain-switched mode-locked Tm-doped fiber laser and amplifier system," Opt. Express 21, 7851-7857 (2013) CrossRef